Strategi Pemasaran Produk Unggulan Desa Melalui Optimalisasi Peran Bumdes Dalam Meningkatkan Perekonomian Masyarakat Desa Kadugede - Makarim, Siti Amirah; Syarif, Endang; Zaman, Jajang Saeful (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the marketing strategy of superior village products through optimizing the role of Village-Owned Enterprises (BUMDes) in Kadugede Village, Kadugede District, Kuningan Regency. This research uses a quantitative descriptive approach with 100 respondents consisting of MSME actors and local product consumers. The sampling technique used probability sampling with a simple random sampling method. The research data consists of primary data obtained through questionnaires and secondary data from village profile documents and related literature. The data analysis method uses simple linear regression analysis to see the effect of marketing strategy on increasing the income of MSME actors. The results showed that the marketing strategy implemented by BUMDes is currently in the fairly good category, but needs optimization in digital marketing aspects. The results of hypothesis testing show that marketing strategy has a significant effect on the sales volume of superior village products with a significance value of 0.000 < 0.05. The contribution of marketing strategy to local economic improvement is 42%.